The Clustering Technology of Information Resource Data on a quantitative Attribute - Бараннік, В. В.; Тупиця, І. М.; Бараннік, В. В.; Сорокун, А. Д. (Science-based technologies, 2019)
The article deals with issues issues related to the development and research of information resource clustering technology using an internal restructuring method based on a quantitative attribute - a sign of the number of series of units for a more advantageous representation of the encoded data. The shortcomings of the existing data restructuring methods - external restructuring methods are analyzed. To eliminate the shortcomings of the methods of external restructuring of information resource data, a fundamentally new approach is proposed - internal restructuring. The clustering tool is internal data restructuring, which consists in identifying patterns in the internal structure of message elements by a quantitative attribute. As a quantitative trait, the trait of the number of series of units is used. The requirements that are imposed on the information resource clustering technology are analyzed. A comparative analysis of existing data restructuring methods is carried out. To improve the efficiency of statistical coding from the standpoint of increasing the protection of an information resource and reducing the length of information presentation, it is proposed to use the information resource clustering technology based on the number of series of units